2021
DOI: 10.1159/000516341
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences on Montreal Cognitive Assessment and Mini-Mental State Examination Scores and the Value of Self-Report of Memory Problems among Community Dwelling People 70 Years and above: The HUNT Study

Abstract: <b><i>Introduction:</i></b> The aims were to examine if the total and item scores on the Montreal Cognitive Assessment (MoCA) and the Mini-Mental State Examination (MMSE) and self-reported memory problems differed between older women and men, and if self-reported memory problems were associated with scores on the 2 tests. <b><i>Methods:</i></b> We included 309 home-dwelling people aged 70 years and older, 155 women, mean age 75.6 (SD 4.1) years, and 154 men, mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This is a shortcoming of this measurement and could affect the results. We used the raw scores of the test, and corrected for age, sex and level of education in the statistical model, which are variables known to be associated with performance on the MoCA test [84,85]. Only body NAA/Cr, not age, sex, education, right hippocampal volume, nor head NAA/Cr, was associated with MoCA performance in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…This is a shortcoming of this measurement and could affect the results. We used the raw scores of the test, and corrected for age, sex and level of education in the statistical model, which are variables known to be associated with performance on the MoCA test [84,85]. Only body NAA/Cr, not age, sex, education, right hippocampal volume, nor head NAA/Cr, was associated with MoCA performance in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…To improve normative data, sex is often taken into account. For example, it has been found that scores on the MoCA (but not on the Mini-Mental State Examination score) are significantly influenced by sex: with women showing a higher performance on delayed recall and men showing a higher score on visuo-construction and serial subtraction (Engedal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To improve normative data, sex is often taken into account. For example, it has been found that scores on the MoCA (but not on the Mini-Mental State Examination score) are signi cantly in uenced by sex: with women showing a higher performance on delayed recall and men showing a higher score on visuo-construction and serial subtraction (Engedal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%